Effects of combination of concentrated Kurozu supplementation and endurance training on mitochondrial enzyme activity and energy metabolism in mice - Suguru Nakano; Kohei Seike; Mai Banjo; Yumiko Takahashi; Kenya Takahashi; Yoshiyuki Matsumoto; Hideo Hatta (Journal of Physical Fitness and Sports Medicine, 2024)
We examined the effects of endurance training with chronic pre-exercise concentrated Kurozu (black vinegar) supplementation on mitochondrial enzyme activity and energy metabolism in Institute of Cancer Research (ICR) mice. Mice were divided into a control group, an endurance training group, and an endurance training + concentrated Kurozu supplementation group. Mice were orally supplemented with water or concentrated Kurozu solution (500 mg/kg body weight/day) for 3 weeks. The mice in the training group were subjected to exercise on a treadmill (20–25 m/min × 30 min, five times/week) starting 30 min after the supplementation. The maximal activity of citrate synthase in the plantaris muscle in the endurance training + concentrated Kurozu supplementation group was significantly higher than that in the control group (p < 0.01). The maximal activity of β-hydroxyacyl coenzyme dehydrogenase (β-HAD) in the soleus muscle in the endurance training + concentrated Kurozu supplementation group was significantly higher than that in the other two groups (p < 0.05 for both). In the final week, significant negative correlation between blood lactate concentration after exercise and soleus β-HAD activity was observed. These findings suggest that endurance training with concentrated Kurozu supplementation increases mitochondrial enzyme activity and might enhance lipid metabolism during exercise.